2020
DOI: 10.17509/jsl.v3i3.23705
|View full text |Cite
|
Sign up to set email alerts
|

STEM-Focused Activities to Support Student Learning in Primary School Science

Abstract: This study examines the effect on student academic success through teaching the "Let's Know the Matter" grade 3 science unit accompanied by STEM (Science, Technology, Engineering, and Mathematics)-focused activities. The study group consisted of 24 third grade students studying in the 2019-2020 academic year. Teaching was done with a 5E (enter, explore, explain, elaborate, evaluate) instructional model, and student opinions about the STEM activities were collected. A group pretest-posttest research design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…No studies were found on the development of life skills other than teamwork . In addition, apart from the STEM-design dimension Ültay, et al, 2020) there is no study aimed at improving students' creative and innovative thinking skills. Science education at school has an effective power in gaining 21st century skills (Hilton, 2010;McFarlane, 2013;NRC, 2010) and shaping the future of societies (National Academy of Sciences, 2005;Tytler, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…No studies were found on the development of life skills other than teamwork . In addition, apart from the STEM-design dimension Ültay, et al, 2020) there is no study aimed at improving students' creative and innovative thinking skills. Science education at school has an effective power in gaining 21st century skills (Hilton, 2010;McFarlane, 2013;NRC, 2010) and shaping the future of societies (National Academy of Sciences, 2005;Tytler, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Both of them are achieved by indirect learning through the existence, habituation, and school culture, by paying attention to the characteristics of the subjects as well as the needs and conditions of students . Teaching subjects with STEM activities has also been recommended for elementary grade students because it can provide them scientific process skills from an early age (Ultay et al, 2020). The transformation of STEM Knowledge that is owned by salt farmers into aspects of content in line with Indonesia's national curriculum is demonstrated through the existence of basic competencies in salt making.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for STEM-based learning in basic education has been implemented abroad such as in Turkey. A study on the application of STEM learning in grade III elementary schools in Turkey with the teaching of "Let's Get to Know the Problem" (Ultay et al, 2020). This study shows that students are trained to be able to solve problems according to the learning theme which will produce products in the form of boats and raincoats as shown in Figure 7.…”
Section: Figure 6 Some Examples Of Students' Learning Projectsmentioning
confidence: 99%
“…The Australian state has started teaching STEM learning to citizens aged around 11-18 years on coding material that produces robots as a final project within 3 months with very supportive facilities and infrastructure (Wijokongko, 2009). The implementation of STEM learning has also been carried out in Turkey through the implementation of learning at the 3rd grade of Elementary School by teaching the unit "Let's Get to Know the Problem" (Ultay et al, 2020). The results of this study indicated that in subjects that are focused on STEM, students can solve problems by producing boat toys and raincoats from the results of their creativity.…”
Section: Introductionmentioning
confidence: 99%